Calculation of the bandwidth of a graded-index optical fiber using experimentally measured quantities - Alam, Shaif-ul; Abedin, Kazi Monowar; Haider, A F M Yusuf (© 2007 Dhaka University Journal of Science, 2017)
This article was published in the Dhaka University Journal of Science [© 2007 Dhaka University Journal of Science]